2010
DOI: 10.2214/ajr.09.3280
|View full text |Cite
|
Sign up to set email alerts
|

MDCT of the Abdomen: Common Misdiagnoses at a Busy Academic Center

Abstract: For each diagnostic error, we explore the reasons for the misdiagnosis and provide experience-based advice to avoid these mistakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…We found this to be a common feature, seen in 35 (81%) of the renal cancers: 25 cancers deformed the outer contour, 6 protruded into the renal sinus and displaced the renal sinus fat, and 4 altered the contour of most or all the kidney. Using multiplanar images can help recognize a renal contour abnormality (17). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found this to be a common feature, seen in 35 (81%) of the renal cancers: 25 cancers deformed the outer contour, 6 protruded into the renal sinus and displaced the renal sinus fat, and 4 altered the contour of most or all the kidney. Using multiplanar images can help recognize a renal contour abnormality (17). …”
Section: Discussionmentioning
confidence: 99%
“…As these prior studies utilized preselected cohorts of renal cancers, they cannot be used to determine the detection rate of renal cancer in clinical practice. Evaluation of patients brought to case review conferences or otherwise identified on an ad hoc basis has demonstrated errors in detecting non-stone renal pathology at unenhanced CT (16,17). However, the renal cancer detection rate cannot be determined with these study designs.…”
Section: Introductionmentioning
confidence: 99%
“…Horton et al . have also examined misdiagnoses in CT reports of the abdomen and recommend the regular use of alternative windows to increase lesion conspicuity and use of multiplanar and/or three‐dimensional reconstructions 20 …”
Section: Discussionmentioning
confidence: 99%
“…Horton et al have also examined misdiagnoses in CT reports of the abdomen and recommend the regular use of alternative windows to increase lesion conspicuity and use of multiplanar and/or three-dimensional reconstructions. 20 In contrast to CT, only 28 cases of discrepancy on MRI were referred. This may be due to two factors: first, that MRI was outsourced to another off-site provider until November 2007; and second, all the MRI scans are double read.…”
Section: Discussionmentioning
confidence: 99%
“…As the importance of abdominopelvic CT (APCT) scans increases, radiologists are faced with the challenge of ensuring comprehensive and accurate imaging interpretations. 1 It has been shown that multiplanar reformatted (MPR) images in multidetector row CT can improve the diagnostic performance, resulting in a more accurate image interpretation compared with axial images alone. 1 However, our experience is that abdominal radiologists are still predisposed to diagnostic errors in the interpretation of routine APCT imaging, despite these advances in imaging technology.…”
Section: Introductionmentioning
confidence: 99%